Art and Science: A Relationship that Permeates the Construction of Human Knowledge About the World - Leite, Mônica Regina Vieira [UNESP]; Gatti, Sandra Regina Teodoro [UNESP]; Reis, Giuliano (Springer Nature, 2024)
Art and Science are often perceived as distant domains. In addition, as knowledge becomes increasingly specific, the lack of communication among Art and Science practitioners can intensify. As a result, the division (or fragmentation) of these fields limits a holistic understanding of themselves and the deep historical connection between them. On the other hand, when artists and scientists collaborate, they produce richer interpretations of reality. The present theoretical paper delves into the existing relationship between Art and Science as diverse but converging paths of understanding the complexity of the world and our place in it. In embracing this perspective, education emerges as a critical bridge to overcome dichotomous perceptions of knowledge production processes, especially in teacher education programs. Science education can benefit not only from the technical aspects of Art, but also from its philosophical and conceptual understanding, contributing to a more humane, creative, and comprehensive view of the natural world.